Pengaruh Pendapatan Perkapita, Jumlah Penduduk Bekerja dan Jumlah Jenis Pajak Daerah terhadap Penerimaan Pajak Daerah pada Kabupaten/Kota Provinsi Kalimantan - Herawati, Elvina; Saipudin (PPJP ULM, 2023)
This research aimed to determine the effect of Per-capita Income, Total Working Population, and Number of Types of Local Taxes on Local Tax Revenues. This research is a quantitative study, and the analysis technique used is multiple linear regression with the ordinary least squares (OLS) method. The data used in the study were from the Central Statistics Agency of South Kalimantan and the Directorate General of Fiscal Balance 2011 – 2018. The results of the study with the best model FEM show that simultaneously Per-capita Income, Total Working Population, and Number of Types of Local Taxes have a significant effect on Local Tax Revenues.